PERSPEKTIF PASIEN DIABETES MELITUS DALAM PENGGUNAAN TERAPI TRADISIONAL SEBELUM MASUK RUMAH SAKIT HORAS INSANI - Lestina, Lestina; Harsudianto Silaen (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Treatment efforts carried out by the community in order to overcome and cure diabetes mellitus do not only rely on the use of synthetic drugs but also by using traditional medicines in the form of single preparations or medicinal plant concoctions. Advances in technology, educational levels and the diversity of ethnicities that inhabit Pematang Siantar City, namely various tribes. and religion influence patterns of use of medicinal plants as traditional medicine. The aim of the research was to find out the perspective of diabetes mellitus patients in using traditional therapy before entering the hospital. The research design used in this research is quantitative descriptive, namely a method that aims to create a picture or description of a situation in a purposeful manner. The total population for this study was all 47 diabetes mellitus patients who visited in January – April 2023 at Horas Insani Hospital. Sampling was taken using a total sampling technique, namely the number of samples was the same as the population or the entire population was sampled, namely 47 people. The instrument used was a questionnaire sheet with univariate analysis. The conclusion of this study is that most respondents use traditional medicines in managing diabetes either alone or in combination with conventional medicines. Most of the herbal medicines obtained by respondents are natural products that are affordable and available so they are easy to obtain. Suggestions for future researchers can be used as material as a basic reference for conducting further research regarding the perspective of diabetes mellitus patients in using traditional therapy before admission and can carry out research such as quasi-experimental methods to see what types of traditional medicine can reduce blood sugar levels in diabetes patients. mellitus so that it can reduce the use of pharmacological drugs for a long time.